Electronic payment methods used for salary resettlement and its impact on improving the mental image of customers: an applied study of the opinions of a sample of (private) commercial banks 'customers contracting with the Ministry of Higher Education and Scientific Research to localize employees' salaries (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research seeks to identify the contemporary events that face the use of electronic payment methods to localize the salaries of state employees and its impact in enhancing the mental image of customers, and to achieve this purpose from the fact that a questionnaire was designed and distributed to an optional sample of (31) individual customers (employees) dealing With the researched private banks, it has been analyzed and reached a number of conclusions and recommendations, the most prominent of which is the lack of modernity of electronic payment methods by customers, which is reflected in the mental image of customers and the achievement of their satisfaction, in the Emiratization project for salaries needs an advanced leadership cadre, as this project differs c Raya on the work of the current traditional banks.